1989
DOI: 10.1055/s-2006-962072
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from TurkishPapaver rhoeas

Abstract: Extract B (0.7 g) was separated on preparative TLC with system (g). (+)-Rhoeadine (290 mg), berberine (140 mg), and coptisine (54 mg) were obtained. Coulteropine was crystallized from methanol, m.p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Furthermore, it is known to calm intestinal and urinary irritation and to be useful in various conditions such as bronchitis, pneumonia, and rash fever (Valnet, 1992). Chemical studies have demonstrated the presence of rhoeadine, rhoeadic acid (Kalva and Sanyar, 1989; Abbreviations: CPP, conditioned place preference; S.C., subcutaneous; I.P., intraperitoneal; VTA, ventral tegmental area * Corresponding author. Fax: +98 21 2281561.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known to calm intestinal and urinary irritation and to be useful in various conditions such as bronchitis, pneumonia, and rash fever (Valnet, 1992). Chemical studies have demonstrated the presence of rhoeadine, rhoeadic acid (Kalva and Sanyar, 1989; Abbreviations: CPP, conditioned place preference; S.C., subcutaneous; I.P., intraperitoneal; VTA, ventral tegmental area * Corresponding author. Fax: +98 21 2281561.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no study to clarify the effects of the extract of this plant on the withdrawal signs of opioids in animal models. Chemical studies have demonstrated the presence of rhoeadine, rhoeadic acid (Kalva and Sanyar, 1989;Slavik et al, 1989), papaveric acid (Zargari, 1994), rhoeagenine (Rey et al, 1992) and anthocyanins (Matysik and Benesz, 1991) as the major compounds of the extract of Papaver rhoeas.…”
Section: Introductionmentioning
confidence: 99%
“…In some regions of Turkey, a decoction prepared from red poppy petals is used for mouth inflammations in children and the infusion of the aerial parts is drunk for lowering the blood sugar level. Previous reports on the alkaloid content of P. rhoeas showed great variation within this species and the presence of aporphine type (roemerine, isocorydine), protopine type (protopine, allocryptopine, coulteropine), protoberberine type (berberine, coptisine, sinactine), rhoeadine type (rhoeadine, rhoeagenine, isorhoeadine, papaverrubine A) alkaloids has been shown (Kalav & Sarıyar, 1989;Sarıyar et al, 2002).…”
Section: Introductionmentioning
confidence: 82%
“…The alkaloids of most of the species belonging to section Rhoeadium have been investigated and the presence of some medicinally important alkaloids has been shown (Sarıyar & Phillipson, 1981;Sarıyar & Kalav, 1990;Atay et al, 1996;Mat et al, 2000;Kalav & Sarıyar, 1989;Sarıyar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%